Potential use of recycled materials on rooftops to improve thermal comfort in sustainable building construction projects - Ahmad, Mushtaq; Ali, Miram; Turi, Jamshid Ali; Manan, Aneel; Al-Dala’ien, Rayeh Nasr Salam; Rashid, khalid (Frontiers in Built Environment, 2022)
The study has two objectives, firstly experimentally measuring of indoor & outdoor temperature of the building in Peshawar and validation with CFD modeling, secondly simulation of the building and utilize locally available natural & recycled insulator materials on the rooftop to keep the indoor environment within a comfortable temperature range, especially in winter & summer seasons. To achieve the objectives, experimental temperature data for January & June is recorded and validated followed by a simulation of the residential building were simulated using ANSYS-Fluent 16 CFD and application of waste thermal insulators such as straw bale, sheep wool, and recycled glass materials used on the rooftop of the building to reduce the indoor temperature. Experimental temperature measurement result shows that on 2nd January 2022 has recorded the lowest indoor temperature of 150C and on 11th June recorded the highest indoor temperature of 410C. The predicated and validated temperature result shows similar findings with a slight difference of less than 15%. The recycled glass has positive and significantly reduced the indoor temperature in summer by 10.29%, thermal amplitude 48.39%, the increment in the time lag was 100% and the increment in the period of comfort hours was 380%. In winter, the daily average temperature increased by 7.42%, the thermal amplitude reduced by 59.32% and the time lag increased by 100%, in comparison with the baseline case results. The study concluded that recycled glass distribution has given the best improvement compared to straw bale and sheep wool.